Development of A Framework for an Asynchronous Discussion Forum through an E-Learning Platform - Durairaj, Kamalambal; bin Assarnurkutty, Shah Jahan; Thoe, Ng Khar; Mohd Sabri, Wan Noor Adzmin bt (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2022)
Throughout the last several decades, the digital era has expanded the process of information sharing in classroom instruction in novel and surprising ways with reference to a wide variety of complex challenges. As a result, effective interactive e-learning management is critical for removing barriers to "knowledge acquisition, exchange, and construction" in this global learning community. According to a review of the pertinent literature, digital and social learning platforms, such as learning management systems (LMS), are effective guides for accomplishing comprehensive online learning. Using a quantitative approach, this paper illustrates the authors’ efforts to develop a social constructivist framework to facilitate formative assessment of an asynchronous discussion forum on various socio-scientific issues (SSI) among teenagers during the initial phase of the project. A learning management system (LMS) was utilised to collect data on project-based activities that encourage inquiry-based and problem-based learning (PBL) following the "Analyze, Design, Development, Implementation, and Evaluation" (ADDIE) model. Different methods of evaluation were implemented to determine the effectiveness of this approach in facilitating the discussions as well as to observe how students' participation in an asynchronous discussion forum improves their overall level of knowledge construction, interaction, and social network analysis (SNA). The important benefits of sharing information are looked at, and future research, innovative projects, and recommendations are shown and predicted.